FAKTOR–FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK MEMBAYAR PAJAK HOTEL DAN PAJAK RESTORAN PADA KANTOR BAPENDA KABUPATEN GOWA - Muhammad Adil; Rustan Rustan; Naidah Naidah; Andi Amelia Cahyanti (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the effect of taxpayer awareness, as well as taxpayer compliance in paying hotel tax and restaurant tax in the regional revenue agency of Gowa Regency. This research is a qualitative descriptive type of research. This research data includes primary data and secondary data. Data collection techniques using library research techniques and documentation study research. The results showed that the factors that influence taxpayer compliance to pay hotel tax and restaurant tax at the regional revenue agency of Gowa Regency are still very ineffective due to the level of compliance and awareness of taxpayers themselves who are still lacking in paying their taxes. In the implementation of the research, there are still obstacles that affect the awareness and compliance of taxpayers in paying hotel taxes and restaurant taxes in the regional revenue agency of Gowa Regency. The benefit obtained from this research is to provide answers to the problems studied and can be used as input for those who experience and are directly involved with this title.